Posterior Cruciate Ligament Graft Fixation Angles, Part 2: Biomechanical Evaluation for Anatomic Double-Bundle Reconstruction. (October 2014) - Kennedy, Nicholas I.; LaPrade, Robert F.; Goldsmith, Mary T.; Faucett, Scott C.; Rasmussen, Matthew T.; Coatney, Garrett A.; Engebretsen, Lars; Wijdicks, Coen A.
Background: Prior studies have suggested that anatomic double-bundle (DB) posterior cruciate ligament reconstruction (PCLR) reduces residual laxity compared with the intact state better than single-bundle PCLR. Although the anterolateral bundle (ALB) and posteromedial bundle (PMB) reportedly act codominantly, few studies have compared commonly used graft fixation angles and the influence that graft fixation angles have on overall graft forces and knee laxity. Hypothesis: Graft fixation angle combinations of 0°/75° (PMB/ALB), 0°/90°, 0°/105°, 15°/75°, 15°/90°, and 15°/105° would significantly reduce knee laxity from the sectioned PCL state while preventing in vitro graft forces from being overloaded between any of the graft fixation angles. Study Design: Controlled laboratory study. Methods: Nine cadaveric knees were evaluated for the kinematics of the intact, PCL-sectioned, and DB PCLR techniques. The DB technique was varied by fixing the PMB and ALB grafts at the following 6 randomly ordered fixation angle combinations: 0°/75° (PMB/ALB), 0°/90°, 0°/105°, 15°/75°, 15°/90°, and 15°/105°. A 6 degrees of freedom robotic testing system subjected each specimen to an applied 134-N posterior tibial load at 0° to 120° of flexion and 5-N·m external, 5-N·m internal, and 10-N·m valgus rotation torques applied at 60°, 75°, 90°, 105°, and 120° of flexion. The ALB and PMB grafts were fixed to load cells that concurrently measured graft forces throughout kinematic testing. t tests compared the kinematics between groups, and 2-factor models assessed the contribution of ALB and PMB grafts after DB PCLR ( P < .05). Results: Consistently, DB PCLR significantly reduced posterior translation compared with the sectioned PCL and was comparable with the intact state during applied posterior tibial loads at flexion angles of greater than 90°; a mean residual laxity of 1.5 mm remained compared with the intact state during applied posterior tibial loads. Additionally, fixing the PMB graft at 15° resulted in significantly larger PMB graft forces compared with fixation at 0° during applied posterior loading, internal rotation, external rotation, and valgus rotation. Similarly, fixing the ALB graft at 75° resulted in significantly larger ALB graft forces compared with fixation of the ALB graft at 90° or 105° during all loading conditions. Conclusion: Fixation of the PMB graft at 0° to 15° and the ALB graft at 75° to 105° during DB PCLR were successful in significantly reducing knee laxity from the sectioned state. However, fixation of the PMB graft at 15° versus 0° resulted in significantly increased loads through the PMB graft, and fixation of the ALB graft at 75° versus 90° or 105° resulted in significantly increased loads through the ALB graft. Clinical Relevance: This study found that all 6 fixation angle combinations significantly improved knee kinematics compared with the sectioned state at time zero; however, it is recommended that fixation of the PMB graft be performed at 0° because of the significant increases in PMB graft loading that occur with fixation at 15° and that fixation of the ALB graft be performed at 90° or 105° rather than 75° to minimize ALB graft forces, which could lead to graft attenuation or failure over time.